Influence of Irrigation Frequency and Lateral Spacing on Drip Irrigated Kharif Onion Crop - Mehla, Mukesh Kumar; Jhorar, R. K.; Kumar, Sanjay; Kumar, Ashish (International Journal of Economic Plants, 2022)
The aim of this study is to identify the most suitable irrigation frequency and lateral spacing for efficient irrigation management in kharif onion crop. In this study, effect of different spacing between drip lateral (45 cm and 60 cm) and irrigation frequency (One, Two, Three and Four days) on onion crop (Allium Cepa L.) under drip irrigation system was studied. Different plant growth and yield parameters were periodically observed.Highest water productivity (10.1 kg m-3) and total bulb yield (169.4 q ha-1) were observed in two days irrigation frequency with 45 cm lateral spacing. Available moisture depth in the root zone (0-60 cm) at 90 DAT, for one day irrigation interval with 45 cm lateral spacing was 11.6 cm at the middle of two laterals which was 9.4% higher than with 60 cm lateral spacing where available moisture was 10.6 cm. In this study, two days irrigation frequency with 45 cm lateral spacing treatment came out to be the most preferable treatment on the basis of water productivity and yield of onion crop.